Synthesis, Characterization and Potential Applications of Exfoliated Graphite/ABS Composites - Bhardwaj Neha; K. S. Manjula; B. Srinivasulu; Shit C. Subhas (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
Exfoliated graphite has received attention as a filler in composites in recent times due to the prominent properties it imparts to the host polymeric matrices. In this study, exfoliated graphite was created using a chemical method, followed by thermal oxidation and sonication to reduce its size and increase the spacing between its layers. To explore its potential applications, composites of exfoliated graphite and acrylonitrile butadiene styrene (ABS) were prepared with different filler concentrations using a simple solution casting technique. Synthesis of exfoliated graphite involves chemical treatment of thermal exfoliation for the formulation and reduction of graphite oxide. Various analytical tools, including scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffractometry (XRD), were used to characterize the materials. The results showed that thermal exfoliation was successful, as indicated by the disappearance of the main graphite peak at 2\(θ\) = 26.4°. SEM images confirmed the uniform distribution of exfoliated graphite within the ABS matrix, while EDAX results demonstrated that the graphite oxide had been effectively reduced. Exfoliated graphite was successfully obtained through thermal exfoliation reduction reaction which was confirmed by SEM and EDAX analysis. Treatment of the natural flake graphite resulted in size reduction and an increase in interlayer spacing of exfoliated graphite as confirmed by XRD.